Investigación de operaciones y turismo - Hernández R., José G. (2007)
The contribution of this paper is to present how a series of Operations Research techniques, can contribute to prepare a pleasant trip for a tourist visiting a certain region. The involved techniques are: The multiattribute models, the travelling salesman problem, the vehicle routing problem and the problem of shorter route. The goal of this research is to create an algorithm, based on the order of preference obtained through a multiattribute model, that have a set of tourist places for a visitor, the model indicates which places to visit and which routes to follow, so that provides the greater satisfaction, according to the constraints the tourist established.